Biodistribution and anti-tumor efficacy of intratumorally injected necrosis-avid theranostic agent radioiodinated hypericin in rodent tumor models. (May 2015) - Liu, Wei; Zhang, Dongjian; Feng, Yuanbo; Li, Yue; Huang, Dejian; Jiang, Cuihua; Gao, Meng; Peng, Fei; Wang, Xiaoning; Jing, Su; Jiang, Xiao; Ni, Yicheng; et al.
Abstract Hypericin has an excellent necrosis-specific targeting capacity; thus, we explored small-molecular tumor necrosis therapy (SMTNT) for inhibiting tumor growth in rodent tumor models. H22 and S180 tumor-bearing Kunming (KM) mice were intratumorally injected with 131I-monoiodohypericin (131I-MIH) to investigate the biodistribution of 131I-MIH as a function of time. Single-photon emission computed tomography (SPECT), autoradiography, fluorescence microscopy and hematoxylin and eosin (H&E) staining were performed to determine the intra-tumoral distribution of 131I-MIH. A therapeutic evaluation study was also performed in the tumor-bearing KM mice using saline and a positive drug as controls. Gamma counting, SPECT images, autoradiography and fluorescence microscopy and H&E staining results revealed intense retention of 131I-MIH in the necrotic tumor over 168 h and good in vivo stability of the agent. Therapy with a single dose of intra-tumoral administration of 131I-MIH caused significant tumor growth delay. A histopathological analysis of the tumors and normal organs further validated the therapeutic efficacy and limited systemic toxicity of 131I-MIH. The prolonged tumor retention and effective therapy indicated that 131I-MIH may be a promising intratumorally injected SMTNT agent.